Prediction of 4D seismic responses for the Otway Basin CO2 sequestration site - Li, R.; Urosevic, Milovan; Dodds, K. (2018)
© 1996-2018 Society of Exploration Geophysicists. All rights reserved. During CO2 sequestration, the effective elastic properties of the reservoir change, initially due to displacement of in-situ pore fluid by free CO2. The magnitude of these changes depends on numerous factors such as, rock type and its composition, temperature and pressure in the reservoir. They are also related to CO2 phase, CO2 injection rate, porosity and permeability. Where CO2 displaces brine solely then conventional 3D surface seismic method is considered as the main method for monitoring the CO2 sequestration process. However, the injection of CO2 into a depleted gas reservoir will in general result in very subtle changes in reservoir elastic properties. Consequently designing an optimum CO2 monitoring strategy is a challenge. To assist this process we have developed a Graphic User Interface (GUI)-driven rock physics simulator which is capable of modeling both short and long-term 4D seismic response changes caused by CO2 injection into a reservoir rock. The reservoir rock may be homogeneous, heterogeneous and/or anisotropic while the pore fluid could be comprised of any fluid mixture. The application of the 4D seismic simulator is demonstrated with reference to the planned CO2 sequestration pilot test site in the Otway Basin, Australia. For the proposed arrangement of the CO2 injection and monitoring wells our numerical models predict that the CO2 injection process at this site will produce both time and space variable seismic responses which will be incorporated into an appropriate monitoring strategy.